A Novel IMFET Biosensor Strategy for Interleukin‐10 Quantification for Early Screening Heart Failure Disease in Saliva. Issue 3 (10th August 2022) - Ben Halima, Hamdi; Bellagambi, Francesca G.; Hangouët, Marie; Alcacer, Albert; Pfeiffer, Norman; Heuberger, Albert; Zine, Nadia; Bausells, Joan; Errachid, Abdelhamid
Abstract: We propose a salivary Interleukin‐10 detection strategy as part of an easily integrable Lab‐on‐Chip and Point‐of‐Care IMFET for multi‐detection Heart Failure (HF) biomarkers. Our developed IMFET showed good linearity between increasing IL‐10 concentration and the charge transfer resistance in both standard solutions and real saliva samples with a LOD of 0.02 pg mL −1 . Moreover, the cross‐selectivity study showed that the developed IMFET was highly selective towards IL‐10 against other HF biomarkers. The precision of our IMFET was also evaluated, and the difference between the determined IL‐10 concentration using the standard addition method and its expected one is<20 %. Abstract :